Penerapan Model Asesmen Problem Based Learning dengan Pendekatan STEM Guna Melatih Kemampuan Berpikir Tingkat Tinggi - Elsina Sarah Tamaela; Iramuar Ishak Kdise; Vils Devega Huwae (Univiversitas Dr. Djar Wattiheluw, 2021)
Assessment is an important part of the learning process because it helps teachers to design learning process according to students’ condition. The assessment developed should take notice to the learning model and approach used. Thus, it will accurately assess the achievements of students. This study has developed a PjBL assessment model using the STEM approach. Whereas, this study conducted based on the unavailability of the PjBL assessment model using the STEM approach. In this study, the experimental research type was applied which using the PjBL-STEM model treatment to students to practice high order thinking skill. The instrument used is the PjBL-STEM assessment tool which was equipped with written feedback and descriptive questions from the analysis level to the creative level. The research subjects were 35 students of grade VII at a schools in Ambon. The data analysis used is quantitative Descriptive which is strengthened by Qualitative. Moreover, the result shows that the assessment can train the thinking in the higher order thinking skill, on the other hand the improvement is not significant.